1997
DOI: 10.1023/a:1012019820603
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These results provide "proof of concept" data for the use of calcium pectinate preparations for drug delivery to the colon and highlight the value of scintigraphy in focusing the development strategy for colonic targeting preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Gamma scintigraphic studies, in humans, of pectin-based tablets (13) as well as pectin-based press-coated tablets (14), have shown that the tablets arrived essentially intact in colon and then are degraded locally by enzymes. Pectin tablets have been produced either by direct compression on manual (11) or slow hydraulic presses (6,10,15) or by compaction of granular pectin on a single-punch machine (16).…”
Section: Introductionmentioning
confidence: 99%
“…Gamma scintigraphic studies, in humans, of pectin-based tablets (13) as well as pectin-based press-coated tablets (14), have shown that the tablets arrived essentially intact in colon and then are degraded locally by enzymes. Pectin tablets have been produced either by direct compression on manual (11) or slow hydraulic presses (6,10,15) or by compaction of granular pectin on a single-punch machine (16).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium pectinate has been formulated into matrix tablets or compression-coated tablets and evaluated both in vitro and in vivo for potential colon-specific delivery. 3,4,[14][15][16][17][18] The calcium level influences the pectin gel strength, which increases with calcium ions added to a critical concentration, and, thereby, influences the drug release. 4,18 Calcium and pectin association can also be achieved through in situ crosslinking systems.…”
Section: Introductionmentioning
confidence: 99%
“…The calcium‐induced associations of pectin chains are stable at low solution pH and are able to resist extensive hydration in vivo in the gastrointestinal tract. Calcium pectinate has been formulated into matrix tablets or compression‐coated tablets and evaluated both in vitro and in vivo for potential colon‐specific delivery 3, 4, 14–18. The calcium level influences the pectin gel strength, which increases with calcium ions added to a critical concentration, and, thereby, influences the drug release 4, 18.…”
Section: Introductionmentioning
confidence: 99%